Macrophage-targeted nanomedicine for the diagnosis and management of atherosclerosis - Hu, Ping Ping; Luo, Shuang Xue; Fan, Xiao Qing; Li, Di; Tong, Xiao Yong (Frontiers in Pharmacology, 2022)
Atherosclerosis is the primary cause of cardiovascular diseases, such as myocardial infarction and stroke, which account for the highest death toll worldwide. Macrophage is the major contributor to atherosclerosis progression, and therefore, macrophage-associated pathological process is considered an extremely important target for the diagnosis and treatment of atherosclerosis. However, the existing clinical strategies still have many bottlenecks and challenges in atherosclerosis's early detection and management. Nanomedicine, using various nanoparticles/nanocarriers for medical purposes, can effectively load therapeutic agents, significantly improve their stability and accurately deliver them to the atherosclerotic plaques. In this review, we summarized the latest progress of the macrophage-targeted nanomedicine in the diagnosis and treatment of atherosclerosis, and their potential applications and clinical benefits are also discussed.